APPLICATION OF TELEROENTGENOGRAPHY IN EARLY DIAGNOSIS OF DENTAL AND JAW ANOMALIES - Polatov Khamidullo Talyat ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Teleroentgenography, a powerful imaging method in dentistry and orthodontics, has revolutionized the early diagnosis of dental and jaw anomalies. By allowing medical professionals to see the internal structures of the teeth and jaws in detail, this technology plays an important role in the early detection of anomalies, developmental problems and pathologies. In this article, we explore the use of teleroentgenography in the early diagnosis of dental and jaw anomalies and its important impact on patient care. Teleroentgenography is important in detecting various dental anomalies that cannot be seen during a routine oral examination.